An investigation on the temporal variation of seismicity in Indo-Burma border region - Barman, NC; Kalita, S (Journal of Nepal Geological Society, 2008)
The Indo-Burma border region within 20°–28°N latitudes and 93°–98°E longitudes shows heterogeneous distribution of earthquakes and on this basis, the region can be divided into three tectonic blocks - Block-I (20°–22.5°N), Block-II (22.5°–25°N) and Block-III (25°–28°N). Temporal variation of earthquakes (M ? 4mb) in these blocks shows that there is some similarity in the variation patterns of Block-I and Block- III (r = 0.77), which indicates that these two blocks behaves almost similarly in the process of strain accumulation and release. In all the three blocks, there can be identified a low seismic activity period (1998-2003). For the belt as a whole, monthwise distribution of earthquakes (M ? 5mb) shows some clustering of earthquakes in the time domain during the high seismicity phases, which have no regular pattern. Magnitude-frequency relationship of earthquakes shows that the values of the constants ‘a’ and ‘b’ vary within the ranges 6.45-7.47 and 0.97-1.18 respectively. Return period analysis of earthquakes indicates that the method of “Least squares” gives better results than that of “Maximum likelihood” method. In the region as a whole, the estimated return periods of earthquakes having magnitudes 6mb and 7mb are found to be 3.8 years and 56 years respectively. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.4